Comparative anatomical study on two different sizes of beetle species, M.Torquata and E.Smithii - Suhoomaran, Dinesh (2015)
This report aims to provide the reader an insight into the author’s project intended to study the muscle structure and perform comparative analysis on the differences or the similarities between two different beetle species. On top of an overview of the literature review done on the anatomy of beetles and a study on their muscle configuration to perform the project, this report consists of an in-depth experimental design procedure and the evaluation of key findings of the aforementioned objective. The primary objective of the project is to study the muscle configurations between beetles of two different sizes. The larger beetle species is the Mecynorrhina Torquata, the 2nd largest flower beetle in the world, while the smaller beetle species is the Eudicella Smithii. By performing anatomical dissections on these beetles, any differences in the structure of beetles can be determined as well as the similarities between the two beetle species. The author’s interest in the project revolves around key findings in these areas as well as any inference that could be made from the findings of these experiments that could prove useful in other fields of beetle research. To support this direction of research, this report will mainly include the extensive study of anatomy of beetle as well as muscle configuration to explain clearly the differences and similarities that were found. The report seeks to understand the different species of beetle clearly and shed light on the work currently being done on these beetles. The author hopes this project will prove vital in stimulation protocols of the beetles in other areas of research in the future. The procedures of anatomical dissection, along with an in-depth understanding of the beetle anatomy have been performed to the best of the author’s abilities.